1986
DOI: 10.1507/endocrj1954.33.561
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of pancreatic endocrine cells of the neonatal rat: VII. The effect of 3-amino-3-deoxyglucose on insulin secretion from perifused B cells.

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

1987
1987
1990
1990

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…In contrast, 10 mM potassium requires glucose to induce insulin secretion from RIN-38 cells. Forskolin increases the cAMP content of neonatal islets, induces an adultlike insulin secretory response to glucose, and shifts the maximal secretory response to higher concentrations of glucose (9). In the present studies forskolin and other cAMP modulators potentiated secretion, but did not alter the glucose sensitivity of RIN-38 cells; similar results were recently reported with fetal islets (34).…”
Section: Potentiation Of Insulin Secretionsupporting
confidence: 90%
See 2 more Smart Citations
“…In contrast, 10 mM potassium requires glucose to induce insulin secretion from RIN-38 cells. Forskolin increases the cAMP content of neonatal islets, induces an adultlike insulin secretory response to glucose, and shifts the maximal secretory response to higher concentrations of glucose (9). In the present studies forskolin and other cAMP modulators potentiated secretion, but did not alter the glucose sensitivity of RIN-38 cells; similar results were recently reported with fetal islets (34).…”
Section: Potentiation Of Insulin Secretionsupporting
confidence: 90%
“…Whether in the presence of 10 mM potassium or 0.1 mM IBMX, glucose has an unaltered dose-responsive effect on insulin secretion. As with neonatal islets (9), IBMX in the absence of glucose acts as a secretagogue with RIN-38 cells. In contrast, 10 mM potassium requires glucose to induce insulin secretion from RIN-38 cells.…”
Section: Potentiation Of Insulin Secretionmentioning
confidence: 94%
See 1 more Smart Citation
“…Perifusion procedure Perifusion of the monolayer cell culture was per¬ formed according to a modification of the method of Kawazu, Kanazawa, Ikeuchi et al (1977), as described previously (Nakao, Kagawa, Wakabayashi & Matsuoka, 1986). In brief, the perifusion chamber was made by placing two discs, made from culture dishes with their rims removed with an electric knife, on both sides of a silicon rubber sheet (thickness 3-5 mm) with a round hole (diameter 3 cm) in the centre.…”
Section: Reagentsmentioning
confidence: 99%
“…In conclusion, these results suggest that cultivation in medium with 5\m=.\5mmol glucose/l could induce precocious development of an adult pattern of insulin secretion compared with that in 16\m=.\7mmol glucose/l and, in addition, that the medium with 16\m=.\7mmol INTRODUCTION It is widely acknowledged that differences exist between the response of the fetal, neonatal and adult pancreas to insulin secretagogues. In the fetal and neonatal rat, cells respond poorly to glucose, with little or no rise in the second phase of secretion (Burr, Kanazawa, Marliss & Lambert, 1971 ;Nakao, Kagawa, Wakabayashi & Matsuoka, 1986). In addition, Grill, Lake & Freinkel (1981) have reported that there is a more generalized defect in the recognition of nutrient secretagogues.…”
mentioning
confidence: 99%